Nucor Rochelle India Limited (NRIL) - Vohra, Neharika, 1966-; Narain, Arohini; Bhatnagar, Deepti (London : Indian Institute of Management, Ahmedabad, 2018)
Set in 2014, "Nucor Rochelle India Limited (NRIL)" is a case that documents how Veer Vaibhav the President of Nucor Rochelle India Limited (NRIL) was able to lead growth though HR practices. It shows the strategies that NRIL, an Indian subsidiary of a Norwegian MNC, adopted to respond to the call towards innovation made by NR Global and be relevant to the Indian market and achieve growth at the same time. Specifically, it traces the turnaround that Veer Vaibhav, the new President of NRIL, brought about in the company's business performance with Jagdish Das, Vice President-HR, Nucor Rochelle International and his team assisting him in shaping NRIL's culture and people practices.
Originally Published InVohra, N., Narain, A., & Bhatnagar, D. (2018). Nucor Rochelle India Limited (NRIL). OB0234. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Vaibhav, Veer; Nucor Rochelle India Limited -- Case studies; Manufacturing industries -- India -- Case studies; Human capital -- India -- Case studies; Leadership -- India -- Case studies